If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5 + -1m) = 2(m + 3) (5 * 4 + -1m * 4) = 2(m + 3) (20 + -4m) = 2(m + 3) Reorder the terms: 20 + -4m = 2(3 + m) 20 + -4m = (3 * 2 + m * 2) 20 + -4m = (6 + 2m) Solving 20 + -4m = 6 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 20 + -4m + -2m = 6 + 2m + -2m Combine like terms: -4m + -2m = -6m 20 + -6m = 6 + 2m + -2m Combine like terms: 2m + -2m = 0 20 + -6m = 6 + 0 20 + -6m = 6 Add '-20' to each side of the equation. 20 + -20 + -6m = 6 + -20 Combine like terms: 20 + -20 = 0 0 + -6m = 6 + -20 -6m = 6 + -20 Combine like terms: 6 + -20 = -14 -6m = -14 Divide each side by '-6'. m = 2.333333333 Simplifying m = 2.333333333
| 10=2x^2+4 | | H=-4.9T^2+20T+10 | | (3x-5)(8x+2)=0 | | (-3/2y^6)^4 | | 40x-30/x=0 | | (2x-5)(4x+7)=0 | | -3=x-21/2 | | (6x-9)(9x+6)=0 | | (8x+5)(3x+3)=0 | | 5y+20=495 | | 12x^2-8xy+9x-6y= | | (1.97)(76x)=12 | | 14m-6k-5m-3k+4k= | | n^3-n^2+3n-3=0 | | 0.3x=0.02 | | x^2+xy-2x-2y=0 | | 4(3x+4)=2(4x+24)-9 | | 20.00+4x=200 | | ax+by=2x | | ax+by=2y | | (121/11)/11=121/(11/11) | | 128/(4/2)=(128/4)/2 | | 4/(4/9)=(4/4)/9 | | 4.9t^2+1.28t-0.26=0 | | 12-(17+1)=(12-17)+1 | | 7x-12=x+2+3x-3x | | ax+by+c=2x | | 4.9t^2-2.81t-0.26=0 | | 3y-15=27 | | 0.6x-0.2=0.4+0.2x | | 4.9t^2-2.14t-0.26=0 | | 2x-590=1925 |